Teacher's Perceptions Toward the Implementation of the Three-Semester Academic Calendar on Students with Specific Learning Disabilities - أيمن محمد إبراهيم السويل (مجلة العلوم التربوية والنفسية, 2024)
Recently, the Ministry of Education in Saudi Arabia implemented a new academic calendar that involves three semesters instead of two semesters in one academic year. This change is considered a new trend since the establishment of the educational system in the Kingdom of Saudi Arabia. The aim of this study was to investigate teachers' perceptions toward the impact of implementing the three-semester on students with learning disabilities as a new practice. Descriptive analysis was used to identify teachers' responses of students with special needs during the new period of the academic calendar. Results showed that there were statistically significant differences in many aspects of students, including academic outcomes, social skills, and academic readiness, according to the experience variable. The differences were in favor of experience of less than 5 years. The study showed that there were statistically significant differences in many aspects of students, including academic outcomes, social skills, and academic readiness, according to the gender variable. The differences were in favor of females. The results were similar regarding readiness and classroom happiness for students with learning disabilities, meaning that participants rated their choices as having a moderate effect on the three-class system. The study included limitations and recommendations for the future. Keywords: Specific learning disabilities, academic outcomes, social skills, three-semester calendar.